Performance analysis model for service supply chains : case of the retirement supply chain - Mezouar, Houda; El Afia, Abdellatif (International Journal of Engineering and Technology, 2018)
A service supply chain (SSC) is a supply network that transfers resources into services with or without physical products, to satisfy cus-tomer needs. So itâ€™s evident that without offering the right service at the right time to the right person, the service is incomplete, inconsistent and ineffective. In the same context, the retirement field faces the challenge of offering the correct pension to the right pensioner the first month of his retirement. This paper approaches this challenge from a SSC perspective as a case study for dealing with continuity in service supply chain. It uses a methodology that combine Analysis-Specification-Design-Implementation (ASDI), Office Support Systems Analy-sis and Design (OSSAD), Business Process Management (BPM), and Supply Chain Operations Reference (SCOR). It analyzes and mod-els the Moroccan retirement SSC, simulates the behavior of "the management of civil pension rights" process, and proposes a set of Key Performance Indicators (KPI) to evaluate the continuity in the service supply chain. Hence, this work provides guidance on the performance analysis of a SSC.Â Â Â